2014
DOI: 10.4028/www.scientific.net/amm.657.256
|View full text |Cite
|
Sign up to set email alerts
|

Study on Identification and Classification of Causes which Generate Welds Defects

Abstract: In the practice of organizations, we notice the existence of a problem which influences negatively the operating parameters of a product and it has to be very accurately identified and proposals have to be drawn-up in order to remove it. This paper presents a method for assessing the quality of welding by applying one of the classic instruments of quality management. The clauses that generate welding defects are identified and classified. The causes are also grouped in two large categories: positive causes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Ishikawa diagram is an excellent tool for mapping the possible sources of uncertainties [7]. An Ishikawa diagram was developed for residual stress measurements by XRD ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Ishikawa diagram is an excellent tool for mapping the possible sources of uncertainties [7]. An Ishikawa diagram was developed for residual stress measurements by XRD ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The advantage of using this chart is that it offers the possibility of examining logically and chronologically the objectives and actions that solve a quality or non-quality problem. Non-qualitative issues and case studies that apply the quality management tools (for example, fish bone diagram) are outlined in several papers [1,2,3,4]. The tree chart was used to analyse defects and establish measures to eliminate nonconformities in many areas of activity (industrial and service activities).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the propagation of ultrasound in the liquid metal bath has considerable influences on the process of transferring the material through the electric arc and on the crystallization process. All these influences are attributed to basic phenomena due to the propagation of ultrasounds in liquid media, namely ultra acoustic cavitation and accelerating the diffusion process [ 9 , 10 , 11 ]. It is also very important to analyze the longitudinal vibration theory for a bar with a variable transverse section, so as to obtain a greater amplification of the efficiency of ultrasonic vibrations [ 12 ].…”
Section: Introductionmentioning
confidence: 99%